2011
DOI: 10.1371/journal.pone.0017736
|View full text |Cite
|
Sign up to set email alerts
|

Geminin-Deficient Neural Stem Cells Exhibit Normal Cell Division and Normal Neurogenesis

Abstract: Neural stem cells (NSCs) are the progenitors of neurons and glial cells during both embryonic development and adult life. The unstable regulatory protein Geminin (Gmnn) is thought to maintain neural stem cells in an undifferentiated state while they proliferate. Geminin inhibits neuronal differentiation in cultured cells by antagonizing interactions between the chromatin remodeling protein Brg1 and the neural-specific transcription factors Neurogenin and NeuroD. Geminin is widely expressed in the CNS during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…Here, we found that while Gem transiently repressed the expression of neuronal genes during mammalian neurogenesis, Gem was not sufficient to alter the differentiation potential of lineage-restricted neural precursor cells. These results are consistent with the recent observation that Gem loss in mammalian NSCs in a conditional mouse model did not affect their capability to self-renew or their differentiation potential in vivo or in vitro (19). We also found that while Gem increases PcG enrichment and otherwise alters the epigenetic status of neuronal genes in neural precursor cells, it did not alter the progression toward terminal neuronal or glial differentiation at either a phenotypic or molecular level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we found that while Gem transiently repressed the expression of neuronal genes during mammalian neurogenesis, Gem was not sufficient to alter the differentiation potential of lineage-restricted neural precursor cells. These results are consistent with the recent observation that Gem loss in mammalian NSCs in a conditional mouse model did not affect their capability to self-renew or their differentiation potential in vivo or in vitro (19). We also found that while Gem increases PcG enrichment and otherwise alters the epigenetic status of neuronal genes in neural precursor cells, it did not alter the progression toward terminal neuronal or glial differentiation at either a phenotypic or molecular level.…”
Section: Discussionsupporting
confidence: 93%
“…Loss of geminin in cortical neural progenitor cells (NPCs) surprisingly resulted in increases in NPC cell number and in decreased production of neurons in ventricular zone regions, suggesting a positive role for geminin in promoting cortical neu-rogenesis (24). However, in another study, loss of geminin had no effect on the cycling NSC population in the subventricular region and hippocampal dentate gyrus, nor did it affect the ability of these NSCs to proliferate or further differentiate into neuronal and glial cell types in vitro (19). Another recent study reported complex actions of geminin during mammalian neurogenesis, where both knockdown and overexpression of geminin resulted in decreased numbers of Sox3-positive neural precursor cells in the mouse embryo.…”
mentioning
confidence: 98%
“…Low levels of overexpression and downregulation obtained in that study may have created a state of chromatin readiness to respond to lineage differentiation factors, rather than neuronal differentiation per se. Recently, targeted deletion of Geminin in neural stem cells suggested that in vivo Geminin may have a primary role in cycle regulation rather than in lineage choice [29], although another analysis demonstrated that deletion expanded the neural precursor population, and overexpression promoted migration and premature neuronal differentiation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Geminin-deficient mice have not yet convincingly demonstrated that Geminin regulates cell differentiation. For example, mice carrying a neuron-specific deletion of Geminin appear to be neurologically normal, and cultured Gmnn D/D neural stem cells differentiate normally into neurons and glial cells (Schultz et al, 2011;Spella et al, 2011). The pattern of differentiation of Gmnn D/D T-lymphocytes is also completely normal (Karamitros et al, 2010).…”
Section: Discussionmentioning
confidence: 99%